Avaliação ergonômica: estudo de caso em uma empresa de sorveteria na cidade de Assú/RN - Souza Neto, Félix de (Universidade Federal Rural do Semi-Árido, 2020)
With the increasing competitiveness in the labor market, the need arises for companies to pay attention to ergonomic aspects, aiming at the health and well-being of their employees, adapting their work to the worker using methods such as job adaptation and postural analysis. As a result, this study aimed to make an ergonomic analysis of work in a company in the food industry, seeking to know and classify the ergonomic risks that affect workers in the workplace, addressing aspects related to work activities. The methodological procedure was based on the application of ergonomic analysis methods. In addition, field observations, interviews and photographic records were carried out. For the analysis of postures, the OWAS method was used, which has been effective in the analysis of jobs that involve movement of the back, arms and legs. It was found that workers have postures that compromise their health and well-being. In addition, the incidence of musculoskeletal pain was observed, reaffirming the implications shown by the methods of analysis. The results obtained show the ergonomic negligence of both parties, employer and employee, as well as the conditions of vulnerability experienced by employees, who suffer from poor working conditions and lack of knowledge in the field of health and safety at work, the latter demonstrated by all the interviewees. It is concluded that there is a need for interventions and an alert aimed at education and awareness, especially of employees who do the work considered heavy.
Keywords: Análise ergonômica; Industria alimentícia; Sorveteria; Ergonomic analysis; Food industry; Ice cream shop; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA